An Approach for Automatic Generating RESTFul API Code based on SQL DDL Code - Fawwaz Ali Akbar; Eka Prakarsa Mandyartha; Hendra Maulana (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
RESTFul API is an emerging technology that is used for communication between various applications or systems. RESTFul API is commonly used in the development of systems and applications. Various application, such as mobile, web, or desktop, are use RESTFul API to handle and compute business processes. Currently, Development of the RESTFul API is easier with the code generator tools and some approaches that will generate RESTful API application automatically. With that tools, developers more easier dan efficient when developing their applications. In this research, we try to create a new approach to create a RESTFul API code generator. This approach is based on the SQL DDL code in the SQL dump file as input. We use this approach because, in the initial phase of building a system, developers must provide their database structure before building their applications. With proposed approach, RESTFul API code generator is more effective and suitable with the developer’s workflow. Based on testing result, The proposed approach can perform well for automatic generating code for RESTful API based on SQL DDL given. And provide basic functionality in RESTFul API such as create, read, update, and delete data.